Vodilne evropske trajnostne soseske - Medved, Primož (Urbani izziv, 2017)
Local projects involving sustainable urban transformation are increasingly prominent in cities and towns, and are often referred to as sustainable neighbourhoods. These initiatives have been described as experiments in urban sustainability and could provide concrete answers to many challenges facing cities and society. This article investigates the design and development of two leading examples of sustainable neighbourhoods that used different implementation strategies: a top-down development in Western Harbour (Swed. Västra Hamnen, Malmö) and a bottom-up (participatory) approach in Vauban (Freiburg). The article investigates how the initial implementation approach in sustainable urban redevelopment influenced and conditioned the urban design, social sustainability and local governance of the neighbourhoods. The research also focuses on how Vauban and Western Harbour have influenced and disseminated sustainable urban solutions to other urban contexts.
Keywords: Europe; Evropa; mesta; soseske; sustainable development; trajnostni razvoj; urbana sociologija; urbani prostor; urbanistični razvoj